THE ISLAMIC LAW AND FREEDOM OF RELIGION: A CRITICAL REVIEW ON THE RIGHT OF APOSTASY AND ITS LEGAL IMPLICATIONS IN MALAYSIA - Aiman As’ad bin Mohd Ghani; Fadhilah binti Abdul Ghani, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2017)
This paper provides a critical review on freedom of religion, particularly with regards to Muslims right to apostate and its legal implications in Malaysia, bringing to the light some of the academicians’ opinion and courts decisions pertaining to the issue. Apostasy is a complex and controversial issue. Despite of a number of cases occurred in the past years, the interpretations to the relevant constitutional provisions are still be debated and some in the opinion that apostasy should be legalized in Malaysia. However, it is strongly argued and suggested that apostasy should not be legalized and taken as a legal right in Malaysia. This paper includes some arguments that are opposed the said suggestion together with the refutation of it. The Islamic view on the status of apostasy is also discussed in this paper. Since apostasy issue remained debated and questioned, this paper proposes that there is a need for a clear law to be implemented in Malaysia to settle this matter.